EFFICACY OF ORGANIC SOIL AMENDMENTS, FUNGICIDES AND CHITOSAN AGAINST MACROPHOMINA PHASEOLINA UNDER IN VITRO CONDITIONS - M. BALRAM and B. MALLAIAH, A. SRINIVAS, G. UMA DEVI, B. VIDYA SAGAR, C. SRINIVAS (The Journal of Research, PJTSAU, 2022)
Among the diseases of maize, Charcoal rot (Macrophomina phaseolina) was found to be the most prevalent and destructive in nature especially in rainfed conditions. Complexity of the disease and its soil borne nature, made the charcoal rot very difficult to manage in field. In the present study, different organic soil amendments, fungicides and chitosan at variousconcentrations were evaluated for their efficacy in inhibiting mycelial growth of Macrophomina phaseolina under in vitro conditions by using poisoned food technique. Neem cake was found superior in inhibiting mycelial growth of Macrophomina phaseolina at all the concentration tested (5%-38.52%; 10%-58.34%; 20%-62.96%) and showed significantly highest mean mycelial inhibition (53.27%) followed by castor cake (5%-31.67%; 10%-53.52%; 20%-56.48%) with mean mycelial inhibition of 47.22%. Among the fungicides, carbendazim completely inhibited the mycelial growth of Macrophomina phaseolina at all concentrations tested (50 ppm -1000 ppm) followed by mancozeb and tebuconazole + trifloxystrobin which could able to completely inhibit the mycelial growth of the pathogen at 500 ppm and above only, with mean mycelial inhibition of 96.70% and 94.19% respectively. Chitosan could able to inhibit the mycelial growth of test pathogen at 2.5 mg ml-1 concentration and above. In conclusion, effective organic soil amendment, fungicide and chitosan can become components for a viable integrated disease management strategy against Macrophomina phaseolina